PENGARUH FITUR KARAKTER TERHADAP SIKAP KONSUMEN ATAS MEREK MELALUI KEPERCAYAAN KARAKTER PADA PRODUK ES KRIM PADDLEPOP - Setyadarma, Bambang (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2018)
This research goal is to measure the influence of Character feature for Customer Atitude on the Brand through the Trust of Character for Paddlepop Ice Cream Product. Samples of this research used 115 respondents. The Sampling technique use non probability sampling (direct of sampling method). Finaly, these research implication try to explain that the Character Feature at the variances: Expertise on Trust of Customer, Relevance for Trust of Customer,and Nostalgy for Trust of Customer have a significant influences to consumer attitude which hypothesis test under level of tolerance about 5%. This research also find that Trust of Customer has an influent to The Customer Atitude. Critical Path Coefficient Analysis of Expertise to The Trust of Customer about 26,5%, Relevancy on The Trust of Customer about 63,8%, Nostalgy on The Trust of Customer about 55,5% and Trust of Customer to The Customer Atitude for Brand about 3,4%. So this research accepted Hypotesis of 1, Hypotesis of 2, Hypotesis of 3, Hypotesis of